2020
DOI: 10.1093/jrr/rraa111
|View full text |Cite
|
Sign up to set email alerts
|

Scaling parameter of the lethal effect of mammalian cells based on radiation-induced OH radicals: effectiveness of direct action in radiation therapy

Abstract: We have been studying the effectiveness of direct action, which induces clustered DNA damage leading to cell killing, relative to indirect action. Here a new criterion Direct Ation-Based Biological Effectiveness (DABBLE) is proposed to understand the contribution of direct action for cell killing induced by C ions. DABBLE is defined as the ratio of direct action to indirect action. To derive this ratio, we describe survival curves of mammalian cells as a function of the number of OH radicals produced 1 ps and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…If the case, the FLASH effect would be strongly dependent on the radiation quality that results radiological process of indirect action and high oxygen enhancement ratio. The proton beam in this study was a 27.5 MeV proton which has G(OH)100 eV of ~3 and OER that are equivalent to that of X-rays and gamma-rays [ 22 , 30 , 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…If the case, the FLASH effect would be strongly dependent on the radiation quality that results radiological process of indirect action and high oxygen enhancement ratio. The proton beam in this study was a 27.5 MeV proton which has G(OH)100 eV of ~3 and OER that are equivalent to that of X-rays and gamma-rays [ 22 , 30 , 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the FLASH effect would strongly correlate on radiation types. For example, charged particles near the Bragg peak are well known to have high LET with highly localized dose distribution along its tracks [ 37 ] that result in a small oxygen enhancement ratio [ 38 , 39 ]. It is explained as a result of small G(OH) value [24, 32] and low consumption of the molecular oxygen per 100 eV at charged particles with high LET that drastically decrease near the Bragg peak [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we implied that the number of OH radicals produced could become a universal parameter for expressing the biological effect 43 . Thus, based on the number of OH radicals produced, we could universally express the biological effect under ionizing radiations with different radiation qualities 30 .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the composition of the LMDS and the following repair pathways involved could depend on the cell type but also on the dose and the LET, which adds another level of complexity to their repair [20]. A recent study investigated the contribution of the direct effects of C-ions compared with their indirect action through the prism of OH • formation in relation to the cell killing resulting from clustered damage [21]. They concluded that the efficacy of C-ions in cell death results from the contribution of OH • produced in the track, which is in favour of the 'bomber' effect.…”
Section: At the Nucleus Levelmentioning
confidence: 99%